Tradition Balimau Kasai in Kampar:Integration of Islamic and Local Culture - Saiin, Asrizal; Armita, Pipin (The Pontianak State Institute of Islamic Studies, 2021)
This study aims to explain that there is an integration between Islamic values and the local culture of Kampar in the balimau kasai tradition. The balimau kasai tradition is a tradition of welcoming the holy month of Ramadan by bathing with traditional herbs and gathering on the banks of the river. In this study it was found that, there are 4 (four) categories that can be integrated between Islamic values and the local culture of Kampar, namely: (1) as a form of gratitude to be met with the month of Ramadan, (2) as a form of joy and happiness with the coming of the month of Ramadan, (3) as a means of cleansing and purifying the body and spirit, (4) as a place to establish friendship, and (5) as a moment to forgive each other. Of the four categories found, it is evident that balimau kasai is a local cultural tradition, as well as a form of planting Islamic values.